Academia journal of biology (Vietnam academy of science and technology, 2018)
Contents new record of the genus Brulleia Szépligeti, 1904 (Hymenoptera: Braconidae: Brachistinae), with description of three new species from Vietnam; New records of bats (Mammalia: Chiroptera) from Cu Lao Cham and Ly Son archipelagos, central Vietnam; A new species of the family Theaceae from central Vietnam;...